Association between parity and bone mineral density in postmenopausal women - Yimei Yang; Shanshan Wang; Hui Cong (BMC, 2022)
Abstract Background Pregnancy has been considered a risk factor for the development of osteoporosis. Despite much research in this field, the relationship between parity and bone mineral density (BMD) is still controversial. Therefore, we conducted this study to investigate whether there was an association between parity and BMD of the femoral neck and lumbar spine in postmenopausal women. Methods Cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES). Three linear regression models, Model 1 (unadjusted), Model 2 (adjusted for age and body mass index (BMI)), and Model 3 (adjusted for all covariates), were established to evaluate the relationship between parity and BMD. In addition, the p value trend of BMD in the different parity groups was mutually verified with the results of multiple regression. Multiple logistic regression models were used to assess the relationship between parity and osteoporosis. Results In total, 924 postmenopausal women aged 45-65 years were eligible for this study. After adjustment for potential confounders, women with ≥ 6 parities had significantly lower lumbar spine BMD than women with 1-2 parities (β = − 0.072, 95% CI: − 0.125, − 0.018, P = 0.009). However, there was no correlation between parity and femoral neck BMD in any of the three regression models. Furthermore, ≥ 6 parities were associated with a significantly higher prevalence of lumbar spine osteoporosis compared with 1-2 parities (OR = 3.876, 95% CI: 1.637, 9.175, P = 0.002). Conclusions After adjustment for BMD-related risk factors, ≥ 6 parities were associated with decreased lumbar spine BMD but not femoral neck BMD in postmenopausal women. This suggests that postmenopausal women with high parity are at increased risk of lumbar osteoporotic fractures and should pay more attention to their bone health.